2021
DOI: 10.3389/fcimb.2021.770821
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Quality and Quantity of Naturally Induced Antibody Responses Against Pfs230 and Pfs48/45 Among Non-Febrile Children Living in Southern Ghana: A Longitudinal Study

Abstract: A clear understanding of the properties of naturally induced antibody responses against transmission-blocking vaccine candidates can accelerate the understanding of the development of transmission-blocking immunity. This study characterized the naturally induced IgG responses against two leading transmission-blocking vaccine antigens, Pfs230 and Pfs48/45, in non-febrile children living in Simiw, Ghana. Consecutive sampling was used to recruit 84 non-febrile children aged from 6 to 12 years old into the 6-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 20 , 54 Importantly, the humoral response to gametocyte TBV immunogens such as Pfs230 may be reinforced by prior and/or subsequent natural infection. 55 Humoral responses against Pfs230 are common in malaria endemic regions, 56 , 57 and we have recently shown that affinity-purified Pfs230-specific antibodies can indeed block transmission. 21 LMIV230-01 is the only other human-derived mAb reported to date with observed TRA 18 ( Figure 5 C) and is encoded by IGHV1-69 and IGKV1-5 , which were the most common germline genes identified from the memory B cells sequences obtained from the eight vaccinees in Coelho et al.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 54 Importantly, the humoral response to gametocyte TBV immunogens such as Pfs230 may be reinforced by prior and/or subsequent natural infection. 55 Humoral responses against Pfs230 are common in malaria endemic regions, 56 , 57 and we have recently shown that affinity-purified Pfs230-specific antibodies can indeed block transmission. 21 LMIV230-01 is the only other human-derived mAb reported to date with observed TRA 18 ( Figure 5 C) and is encoded by IGHV1-69 and IGKV1-5 , which were the most common germline genes identified from the memory B cells sequences obtained from the eight vaccinees in Coelho et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pfs230 is the most advanced TBV candidate and Pfs230D1-EPA 22 26 is currently in clinical trials (NCT02334462, NCT02942277, NCT03917654, NCT05135273). TBV candidates other than Pfs230 3 , 6 13 , 15 25 , 27 29 , 62 , 63 , 65 76 under clinical evaluation include Pfs25 3 , 62 64 and Pfs48/45 3 , 62 , 72 75 , and other antigens have been identified and are in development 35 , 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Avidity of Ag-specific Ab was determined by avidity ELISA as reported ( 15 17 ) with minor modifications. Briefly, plates were coated as the regular ELISA assay described above.…”
Section: Methodsmentioning
confidence: 99%